Trade specialisation and economic convergence: evidence from two eastern European countries - Guglielmo Maria Caporale; Christophe Rault; Robert Sova; Anamaria Sova (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper analyses trade specialisation dynamics in two Eastern European countries (Romania and Bulgaria - EEC-2) vis-à-vis the core EU member states (EU-15) over the period 1990-2006. Specifically, we focus on whether there is a shift towards intra-industry trade leading to economic convergence and technological catch-up. We use recently developed static (FEM, REM and FEVD) and dynamic (GMM) panel data methods which take into account possible heterogeneity. Our empirical results indicate that intra-industry trade has indeed increased, but it is of the vertical rather than the horizontal type, resulting in complementary rather than competitive production patterns.
Keywords: F13; F15; C23; 330; Gravity models; panel data models; trade specialisation; comparative advantage; Außenwirtschaft; Komparativer Kostenvorteil; Intraindustrieller Handel; Entwicklungskonvergenz; EU-Erweiterung; Momentenmethode; EU-Staaten; Rumänien; Bulgarien